Effect of Supplementation of Slow Release Non-Protein Nitrogen Compound on the Lactation of Cows - Gadegaonkar, G.M.; Patil, M.B.; Gulvane, S.U.; Karambele , N.R.; Jagadale, S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A feeding trial to study the effect of slow release non-protein nitrogen compound was conducted for 180 days in twelve early lactating Gir and crossbred cows that were divided into two equal groups viz., T0 (Control) and T1 (treatment). T0 received farm made concentrate mixture and T1 received concentrate mixture containing 1% SRNPN (Slow release non-protein nitrogen compound). The animals in both the groups were fed mixed hay as dry roughage and paragrass as green roughage. Dry matter intake in T0 and T1 was comparable. The average daily milk yield, 4% FCM yield, TDN and DCP intake of cows inT1 was significantly (P<0.01) higher than T0. The efficiency in terms of DM, TDN and DCP required per kg FCM were significantly (P<0.01) better in T1 than T0. The specific gravity, milk protein, solids not fat, total solids and total ash contents of milk were comparable in both the experimental groups, however, the average milk fat percentage in T1 was significantly (P<0.01) higher than T0. Digestibility coefficients of all the nutrients were higher in SR-NPN supplemented group than SR-NPN non-supplemented feed. Profit realized per day over feed cost per cow was higher in T1 (Rs.108.34) than T0 (Rs. 90.29). It can be inferred that efficient utilization of poor quality roughages, better productivity and higher profit margin can be achieved by inclusion of SR-NPN at 1 percent level in the concentrate mixture of lactating cows.